Tingkat konsentrasi dan fungsi kognitif wanita pekerja usia 40-50 Tahun yang mengikuti senam zumba dan yoga - Prayikno, Rina; Noordia, Anna; Kumaat, Noortje Anita; Yuliastrid, Dita; Susanto, Indra Himawan (Jurnal Porkes, 2023)
The problem is that women aged 40-50 years experience psychological changes such as decreased levels of concentration and cognitive function, especially for a worker. The aim is to determine the level of concentration and cognitive function of working women aged 40-50 years following Zumba and yoga exercises. Observational research method with cross sectional design. The research subjects were 20 working women aged 40-50 years, using a purposive sampling technique. The data collection technique used a concentration grid exercise questionnaire and a mini mental state examination. The result is that the Zumba class has very little concentration (60%) and less concentration (40%). The yoga class has very less concentration (20%) and less concentration (80%). The results of the Zumba class cognitive function tests in the normal category have a percentage (60%) and the probable category of cognitive impairment (40%). The results of cognitive function in the yoga class in the normal category have a percentage of (90%) and the probable category of cognitive impairment (10%). In conclusion, the concentration level of working women aged 40-50 years is mostly in the very low concentration category. The results of the cognitive function of the Zumba and yoga classes were mostly in the normal category.